Standardization of monograph specifications for cassia fistula leaves - Rodriguez, Jade P.; Palacpac, Jocelyn B. (Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2023)
Background Herbal Plant Monographs are official documents containing the plant's descriptions as well as standard tests to ensure its identity, safety, and quality. Limits are set on these monographs through standardization by systematic collection and testing of various plant materials from different regions of the country. Any potential Herbal Medicine must comply with an official monograph to be registered and regulated by the Food and Drug Administration. As such, the plant Cassia fistula L. leaves a potential herbal medicine that needs proper regulation through an official monograph.

Objectives This study aimed to standardize monograph specifications for C. fistula L. (Fam. Fabaceae) leaves. Specifically, (1)collect authenticated samples from different geographic locations; (2) establish physicochemical standards; (3)identify the phytochemical constituents; (4)develop an Identification Test using Thin Layer Chromatography and High-Performance Liquid Chromatography Procedure

Results Ten samples of C. fistula L. were standardized for Phytochemical constituents, foreign organic matter and tested for physicochemical properties namely Ash content, Loss on Drying, Moisture Content, Extractives, Heavy Metal and Microbial Testing. Identification tests were done through TLC and HPLC. Data gathered from the different samples were collated and limits were set accordingly. For Thin Layer Chromatography, a similar Chromatogram with a similar number of Spots/Bands and their respective Rf values at different observation conditions (White Light - 8 bands, UV 254 - 10 bands, UV 366 - not less than 12). High-Performance Liquid Chromatography conditions include the Isocratic Mobile Phase of Acetonitrile:0.1% Trifluoroacetic Acid (55:45), RP-18 Column, a flow rate of 1.0mL/min, 10microliter injection volume, 30minute run time, Standard Solution using Rhein Reference standard (20meg-2.5mcg/ml.), Sample Solution of 1g of dried methanol extract in 100ml methanol. The resulting chromatogram shows the peak of the standard rhein at a Retention time of 5.101 minutes.

Conclusion Standardization of 10 samples yielded limits to ensure that the identity, safety, and quality of Cassia fistula L. leaves are kept. Limits were set as follows, Total Ash not more than 10%, Acid Insoluble Ash not more than 2%, Water Soluble Ash not more than 3%, Loss on Drying and Moisture Content less than 10%, Water Soluble Extractives, not less than 12%, and Ethanol Soluble Extractives not less than 6%. For Microbial testing and Heavy metal testing, all samples must pass the requirements according to the set requirements under A0172 s 2004 of the Philippine FDA. For Identity, Thin Layer Chromatogram must be identical to the Chromatogram presented while for HPLC, a detection of Rhein at RT 5.101 using the HPL Conditions.
Thesis (Master of Science in Pharmacy)--University of the Philippines Manila, June 2023.
Keywords: Cassia fistula -- Therapeutic use; Herbal Medicine; Thin Layer Chromatography; High-Performance Liquid Chromatography; Heavy Metal Testing; Fabaceae; Phytochemical Constituents; Thin Layer Chromatogram; High-Performance Liquid Chromatography (HPLC).